2017
DOI: 10.18632/oncotarget.17834
|View full text |Cite
|
Sign up to set email alerts
|

BPTF inhibits NK cell activity and the abundance of natural cytotoxicity receptor co-ligands

Abstract: Using syngeneic BALB/c mouse breast cancer models, we show that the chromatin remodeling subunit bromodomain PHD finger transcription factor (BPTF) suppresses natural killer (NK) cell antitumor activity in the tumor microenvironment (TME). In culture, BPTF suppresses direct natural cytotoxicity receptor (NCR) mediated NK cell cytolytic activity to mouse and human cancer cell lines, demonstrating conserved functions. Blocking mouse NCR1 in vivo rescues BPTF KD tumor weights, demonstrating its importance for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Building on these discoveries, data we present suggest that NURF, as measured by localization of BPTF, is broadly localized to coding sequences in the genome and within the gene bodies. These results agree with previously reported localization of BPTF to gene bodies in human breast cancer cells (34), and from our own studies of BPTF as a regulator of tumor cell immunogenicity (50,51). Broad NURF localization is consistent with the proposed model of ISWI-containing remodeling complexes continuously sampling chromatin (52).…”
Section: Discussionsupporting
confidence: 92%
“…Building on these discoveries, data we present suggest that NURF, as measured by localization of BPTF, is broadly localized to coding sequences in the genome and within the gene bodies. These results agree with previously reported localization of BPTF to gene bodies in human breast cancer cells (34), and from our own studies of BPTF as a regulator of tumor cell immunogenicity (50,51). Broad NURF localization is consistent with the proposed model of ISWI-containing remodeling complexes continuously sampling chromatin (52).…”
Section: Discussionsupporting
confidence: 92%
“…Total proteins of fresh-frozen glioma and normal brain tissues were extracted using RIPA lysis buffer (Thermo Fisher Scientific, Inc.) and separated by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) then transferred onto polyvinylidene fluoride (PVDF) membranes (EMD Millipore, Billerica, MA, USA) as previously described ( 15 ). The protein concentration was detected by bicinchoninic acid (BCA) protein assay (Pierce Chemical, Rockford, IL, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Investigation on its role in cancer showed that BTPF is overexpressed in lung cancer, where it plays an essential role in cell growth and survival by targeting many signaling pathways [ 43 ]. In addition, it has been demonstrated that NURF suppresses tumor antigenicity and that its depletion improves antigen processing enhancing T-cell-mediated antitumor immunity [ 44 , 45 ]. BPTF is mutated in bladder tumors and its knockdown in cultured bladder-cancer cells results in reduced proliferation and it is hypothesized that this effect is mediated in part by c-Myc [ 46 ].…”
Section: Main Textmentioning
confidence: 99%